2014
DOI: 10.3389/fnhum.2014.00027
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of intentional and stimulus-driven inhibition: a comparison

Abstract: People can inhibit an action because of an instruction by an external stimulus, or because of their own internal decision. The similarities and differences between these two forms of inhibition are not well understood. Therefore, in the present study the neural correlates of intentional and stimulus-driven inhibition were tested in the same subjects. Participants performed two inhibition tasks while lying in the scanner: the marble task in which they had to choose for themselves between intentionally acting on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 37 publications
(73 reference statements)
2
29
0
Order By: Relevance
“…In the early studies using this method, facilitation was observed for muscles associated with the forthcoming response and inhibition was observed for muscles associated with nonselected responses (Chen & Hallett, 1999; Duque, et al, 2005; Leocani, et al., 2000). These findings led to the hypothesis that inhibitory mechanisms are recruited during response selection to suppress activity in muscles associated with actions that are not selected (Koch, et al, 2006; Schel, et al, 2014; van den Wildenberg, et al, 2010), a process we have termed competition resolution (CR) (Duque, et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…In the early studies using this method, facilitation was observed for muscles associated with the forthcoming response and inhibition was observed for muscles associated with nonselected responses (Chen & Hallett, 1999; Duque, et al, 2005; Leocani, et al., 2000). These findings led to the hypothesis that inhibitory mechanisms are recruited during response selection to suppress activity in muscles associated with actions that are not selected (Koch, et al, 2006; Schel, et al, 2014; van den Wildenberg, et al, 2010), a process we have termed competition resolution (CR) (Duque, et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…More generally, throughout development, people have been instructed not to do certain things many times; eventually, they will learn some of this, and this could influence decision-making in a direct, automatic fashion. Sequential dependencies, which can influence the 'whether' decision (Schel et al 2014), may also be (partly) associatively mediated. After executing an action a couple of times, subjects may be more (or less) likely to execute the action again.…”
Section: Implications For Intentional Inhibitionmentioning
confidence: 99%
“…The authors suggest that the expression of abnormal and excessive movement may in part reflect a failure of inhibition. Motor inhibition and intention have been conceptualized as two sides of the same coin, with nonconscious motor inhibition 37 and intentional and cued motor inhibition [38][39][40] implicating the supplementary motor complex (the same region also implicated in motor intention). However, a study using a motor inhibitory go/no-go functional magnetic resonance imaging (fMRI) task did not support either abnormalities in intention or inhibition.…”
mentioning
confidence: 99%